2008
DOI: 10.2320/matertrans.maw200822
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Solid Equilibrium and Intermediate Phase Formation during Solidification in Mg-1.3 at%Zn-1.7 at%Y Alloy

Abstract: Mg-Y-Zn alloys have attracted much attention in recent years due to their excellent mechanical properties, which are said to be the effect of the intermediate phase (X phase) in the Mg solid solution ( phase). The formation behavior of the X phase has been reported to be a eutectic type reaction in the Mg-Y-Zn pseudo-binary system. However, the phase diagram of this system still requires clarification. In the present study, the 97.0Mg-1.3Zn-1.7Y (at%) alloy was prepared to clarify the liquidus and solidus in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…6) On the other hand, an intermetallic compound (W phase; Mg 3 Zn 3 Y 2 ) has also received attention in recent years as a new strengthening phase in MgZnY ternary alloys in addition to the ¡ and X phases. 7,8) Authors have reported 9) that the X phase is not solidified in a manner of eutectic reaction as reported previously, 10) but in a manner of peritectic reaction. Moreover, the W phase is transiently formed from the liquid phase in high temperatures, and is disappeared after the subsequent isothermal heat treatment.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…6) On the other hand, an intermetallic compound (W phase; Mg 3 Zn 3 Y 2 ) has also received attention in recent years as a new strengthening phase in MgZnY ternary alloys in addition to the ¡ and X phases. 7,8) Authors have reported 9) that the X phase is not solidified in a manner of eutectic reaction as reported previously, 10) but in a manner of peritectic reaction. Moreover, the W phase is transiently formed from the liquid phase in high temperatures, and is disappeared after the subsequent isothermal heat treatment.…”
Section: Introductionsupporting
confidence: 54%
“…The analyzed chemical compositions of nominal Mg 97.0 -Zn (at%), respectively, which were adopted to distinguish the alloys. Figure 2 shows backscattered electron images (BEIs) and analyzed chemical compositions of the black and gray regions obtained by EPMA for the Mg 97.2 Zn 1.3 Y 1.5 alloy after the isothermal heat treatment at 833 K. The authors have already reported 9) from the resultant chemical compositions that the black and gray regions in Fig. 2 are the ¡ and X phases, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration ratio of Y/Zn in the LPSO is almost equivalent, and that in the matrix is 3, and that in the transition layer increases from 0.5 (as-cast) to 1. 3,4,7,12,14) The LPSO in the rapid solidification processes shows 18R-type LPSOs with an especially dilute composition. These facts indicate that nonstoichiometric 18R-type LPSO can exist metastably.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Recently, one of our authors has investigated the solubility limit for the a phase and the chemical composition of the X phase in the a phase. 8) In the study we revealed that the W phase has non-stoichiometry for the Mg and Zn at 25 at% Y composition with L2 1 crystal structure, which has different thermodynamic model proposed by previous literature. 8) Thus it is necessary to re-build a thermodynamic database to simulate the system by means of CALPHAD technique.…”
Section: Introductionmentioning
confidence: 93%
“…8) In the study we revealed that the W phase has non-stoichiometry for the Mg and Zn at 25 at% Y composition with L2 1 crystal structure, which has different thermodynamic model proposed by previous literature. 8) Thus it is necessary to re-build a thermodynamic database to simulate the system by means of CALPHAD technique. The solid solubility range in the W phase and melting point of the X phase and the I phase were evaluated based on our experimental results.…”
Section: Introductionmentioning
confidence: 93%